X-Linked Thrombocytopenia and Thrombocytopathia: Attenuated Wiskott-Aldrich Syndrome - Stormorken, H; Hellum, B; Egeland, T; Abrahamsen, T G; Hovig, T (Thrombosis and Haemostasis, 1991)
Detailed studies on the rare disorder X-linked thrombocytopenia showed that it resembles the Wiskott-Aldrich syndrome (WAS) in inheritance, clinical bleeding tendency, platelet morphology, marked thrombocytopenia and microplatelets. The calculated platelet mass was 5% of normal. Functional and biochemical studies indicated qualitatively normal aggregation and release mechanisms, whereas a moderate storage pool defect was present. The classical platelet membrane glycoproteins and lymphocyte sialophorin (CD 43) were normal.The reason for the bleeding tendency was concluded to be deficient hemostatic plug formation resulting from the low platelet mass and a moderate storage pool defect.The only clear distinction from WAS was the normal immunofunctional tests, the moderate tendency to infections and the absence of eczema. We therefore consider the trait as an attenuated form of WAS. That women are affected may indicate a particular variant.